ДОРЕВОЛЮЦІЙНА ІСТОРІОГРАФІЯ ПИТАННЯ ПРО СТАВЛЕННЯ ТА ДІЇ РОСІЙСЬКОГО САМОДЕРЖАВНОГО АПАРАТУ ВІДНОСНО УКРАЇНСЬКИХ ПОЛІТИЧНИХ ПАРТІЙ НА ПОЧАТКУ ХХ ст. (Zaporizhzhia Historical Review, 2021)
The article is an attempt to show how the pre-Revolutionary historiography reflects the activity and attitude of the Russian autocratic machinery representatives to the Ukrainian political parties at the beginning of the XXth century.